The influence of fasting during Ramadan on physiological and performance variables in football players: The F-Marc study during Ramadan 2006 (Journal of Sports Sciences, 2008)
Sonderheft mit acht Einzelbeiträgen zum Thema Einfluss von Fasten während des Ramadan auf physiologische und Leistungsvariable bei Fußballspielern.